Analysis of Archive Processing Procedures in the Administration of the General Bureau of the Regional Secretariat of North Sumatra Province - Laila Fitria (Penerbit Jurnal Indonesia, 2022)
In the Company, one of the activities in administration is the issue of archives. One type of activity carried out in various offices, both government offices and private offices, is the work of storing documents, archives or documents. This activity is better known as archival administration or archives. Archives have a very important role in administration, namely as a center of memory and a source of information in order to carry out planning, analysis, formulation, policy, assessment, control and accountability activities as accurately as possible. But even so, there are also offices that have not managed their archives properly. Archiving is one type of office or administrative work that is mostly carried out by every business entity, both government and private business entities. Archiving involves work related to the storage of manuscripts or letters and other office documents.